Psychological Distress, A Risk or A Consequence: An Assessment of The Aetiological Predictability of Depression, Anxiety and Stress Among the Newly Diagnosed Breast Cancer Patients of Pathan Ethnicity - Ghaffar, Fazia; Ayub, Hira (Indus Journal of Bioscience Research, 2025)
Background: Breast cancer is a major global health concern and the leading cause of cancer-related deaths in women. While early detection improves survival, psychological distress’s role in its etiology remains unclear, despite its significant impact on patients and their families. Methodology: This prospective analytical cross-sectional study, conducted a comprehensive assessment of the status of psychological distress among the newly diagnosed breast cancer patients of pathan ethnicity of Khyber Pakhtunkhwa, Pakistan. Based on written consent a sample of 235 breast cancer patients were assessed for the prevalence of depression, anxiety, and stress using the Depression Anxiety Stress Scale (DASS). Results: The findings reveal that a substantial proportion of patients experience severe to extremely severe levels of psychological distress, with 25.7% reporting severe depression and 41.7% experiencing extreme depression. Anxiety and stress levels were also notably high, emphasizing the emotional challenges and stressful life events faced by patients. The parameters of the DASS showed though were found to be significantly varied across demographics, all levels varied significantly. The mean score of depression (17.55±5.051), anxiety (19.78±13.17), and depression (27.6±13.17) were significantly different with in the sample however these scores lied in the moderate and severe categories of the scale. The regression statistics further highlighted the factors such as age, family structure, parity, and body mass index were the strongest influencing and predictors of the pervasive psychological distress among the pathan women of this region. Conclusions: These results highlight the critical need for psychological support in breast cancer care, advocating for early mental health interventions, counseling, and family-centered support programs to improve overall well-being and treatment outcomes.